Divorce: An Unending Phenomenon in Human Society - Gideon Imoke Emeng; Nzeyo Gabriel Eteng (HUMAN: South Asian Journal of Social Studies, 2022)
Abstract: Divorce and living in a single-parent home are becoming more prevalent in the lives of parents and children. As a social problem involving the formal dissolution of a marriage and the separation of the couple, divorce impacts society, separated parents, extended relatives, and children. For a singular reason, this work attempts to expose why divorce seems to be an unending phenomenon in human society. The research was exploratory in nature, using both primary and secondary sources of published works and books to carry out the research. This research found that several factors contribute to divorce and the dissolution of marriage. Education and employment among women or wives, different education levels among couples, employment among couples, infidelity among spouses, young, immature individuals getting married, interference from in-laws and other dependent family members, misunderstanding or conflicting opinions, financial instability or poverty, cultural issues, domestic violence, marital rape or sexual abuse, infertility, barrenness, and drug abuse, to name a few, are a few of the factors that negatively impact marriages. The research indicated that the primary effects of divorce are economic and psychological issues such as stress. This paper argues that the government and religious organisations should do more in terms of education and legislation to mitigate the negative effects of divorce on children.Keywords: Marriage; cultures; society; divorce.